Virtual Verification Framework for Vehicle Motion Systems - Blakqori, Albijon; Kotur, Mille (My University, 2024)
The automotive industry continually strives to enhance vehicle development processes to be faster, more cost-effective, and of higher quality. This thesis presents the development of a Virtual Verification Framework (VVF) to improve the Computer Aided Engineering (CAE) verification process for vehicle motion systems. The focus is on the initial stages of vehicle development, specifically replacing traditional Vehicle-in-the-loop (ViL) testing with more efficient Software-in-the-loop (SiL) methods. The framework is developed using IPG CarMaker, a widely adopted simulation software, and Simulink, allowing detailed subsystem simulations such as braking systems. The objective is to create a correlated CAE environment that can perform high-fidelity simulations and provide reliable data for system verification. This involves implementing accurate simulation models, selecting relevant verification scenarios, and analyzing both simulations’ and real-world data’s performance and accuracy. Key research questions addressed include the analysis of output data reliability for correlation studies between SiL and ViL and the potential expansion of the SiL stage to replace some aspects of ViL in system verification. The thesis demonstrates that while a complete VVF is not yet realized, significant progress has been made, particularly in implementing system-specific models and functional testing within CarMaker for Simulink (CM4SL). Challenges identified include simulated and real-world data discrepancies, particularly with tire modeling and sensor frequency differences. Despite these, the framework shows promise for future scalability and application, aiming to reduce reliance on physical prototypes, enhance safety in early-stage testing, and streamline the vehicle development process. The work concludes that a more robust and trustworthy virtual verification environment can be established, significantly benefiting the automotive industry’s development cycles.
Keywords: Virtual Verification Framework; vehicle motion systems; Computer Aided Engineering; CarMaker; MATLAB; Simulink; brake system; vehicle dynamics verification; Software-in-the-Loop; Vehicle-in-the-Loop